Hubungan Metode Ceramah Dan Media Audiovisual Dengan Tingkat Pengetahuan Cuci Tangan Pakai Sabun Pada Siswa SDN 22 Jeppe'e Kabupaten Bone - Arif , Muh.Ikbal; Rivai, Abdur; Syam, Fitri Salsabila (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
The habit of washing hands with soap in elementary school children still does not receive enough attention, which will lead to various health problems, such as diarrhea and many more. Therefore, providing education about health promotion to elementary school children through lecture methods and audiovisual media is very important. This study aims to determine the relationship between the lecture method and audiovisual media with the level of knowledge of hand washing with soap in students of SDN 22 Jeppe'e, Bone Regency. The type of research used is analytical observational research with a cross sectional approach. The sampling technique used was purposive sampling with a sample size of 104 respondents and analyzed using the chi square test. Based on the results of research with the chi square test, it shows that there is a relationship between the lecture method and the level of knowledge of hand washing with soap in students of SDN 22 Jeppe'e, Bone Regency p value = 0.012 < α = 0.05, there is a relationship between audiovisual media and the level of knowledge of hand washing with soap in students of SDN 22 Jeppe'e, Bone Regency p value = 0.002 < α = 0.05. It can be concluded that there is a relationship between the lecture method and audiovisual media with the level of knowledge of hand washing with soap in elementary school students. It is expected to improve knowledge through lecture methods and audiovisual media and use more effective health promotion methods to improve student knowledge. Keywords: Lecture method; audiovisual media; knowledge; handwashing with soap;